Effects of soil amendment from herbal and eucalyptus industrial waste on methane emission and rice yield - Kurniawati, Feriana Dwi; Suntoro, Suntoro; Setyanto, Prihasto; Cahyani, Vita Ratri (Universitas Sebelas Maret, 2023)
The use of chemical fertilizer in rice fields contributes to increased global warming via enhanced emission of methane (CH4) into the atmosphere. Therefore, composting has been proposed to reduce methane emissions in the agricultural field. This study aimed to determine the CH4 emission and rice yield affected by compost from three different types of compost: herbal compost, eucalyptus compost, and manure compost. This randomized block design study was conducted from November 2019 to May 2020. There were 8 fertilizer treatments applied to the rice fields, namely: herbal compost 10 tons/ha. (O1), eucalyptus compost 10 tons/ha (O2), manure compost 10 tons/ha (O3), no compost no chemical fertilizer (as a control) (O4), herbal compost 5 tons/ha + chemical fertilizer/CF (C1), eucalyptus compost 5 tons/ha + CF (C2), manure compost 5 tons/ha + CF (C3), and only chemical fertilizer (C4), then all treatments replicated three times. For the chemical fertilizer (CF) the dose is 166 kg/ha urea + 166 kg/ha ZA + 330 kg/ha TSP. The result indicated that the compost manure 10 tons/ha (O3) and the combination compost manure 5 tons/ha + CF (C3) produced the highest rice yields (6.89 -6.94 tons/ha) but impacted the highest methane emissions (505.3 – 544.6 Kg.CH4 /ha/season). The important finding showed that among all the treatments, a combination of compost eucalyptus 5 tons/ha + CF (C2) and compost eucalyptus 10 tons/ha (O2) mitigated methane emission to the lowest level (296.6 -305.2 Kg.CH4/ha/season) and gave high rice yields (6.77-6.78 tons/ha) that were not significantly different from those of compost manure (O3 and C3). In addition, the combination of compost herbal 5 tons/ha and chemical fertilizer (C1) affected the lower methane emissions than manure compost and gave a high level of grain yield that was not significantly different from those of manure compost (O3 and C3) and eucalyptus compost (O2 and C2).